Effectiveness of Panretinal Photocoagulation Plus Intravitreal Anti-VEGF Treatment Against PRP Alone for Diabetic Retinopathy: A Systematic Review With Meta-Analysis - Zhang, Wuyue; Geng, Jinsong; Sang, Aimin (Frontiers in Endocrinology, 2022)
Objective: To compare the effectiveness of panretinal photocoagulation (PRP) combined with intravitreal anti-vascular endothelial growth factor (anti-VEGF) against PRP monotherapy for Diabetic retinopathy (DR). Methods: We searched Pubmed, Cochrane Library, Web of Science, and Embase of Controlled randomized Trials through April 2011 to January 2021 that compared the efficacy and safety between PRP combined with intravitreal anti-VEGF and PRP monotherapy for DR. The outcomes were the best-corrected visual acuity (BCVA), neovascularization on the disc (NVD), neovascularization elsewhere (NVE), central macula thickness (CMT), total retinal volume over time (FAS) and adverse events (AEs) between the two groups. Results: A total of 351 studies were identified, of which 11 studies were included(N=1182 eyes). Compared with PRP monotherapy, PRP plus anti-VEGF combination treatment produced a mean reduction in BCVA in units of logMAR of -0.23 [95% CI -0.32, -0.15] or a mean improvement in BCVA in units of letters of 4.99 [95% CI 3.79, 6.19], and also yield a mean reduction in NVD of -28.41 [95% CI -30.30, -26.52], in NVE of -1.33 [95% CI -1.52, -1.14], in CMT of -1.33 [95% CI -1.52, -1.14] or total FAS. No significant difference was observed on the risk of AEs as vitreous hemorrhage, elevation in intraocular pressure and cataract. Conclusions: PRP with anti-VEGF combination treatment can achieve the ideal efficacy on DR by improving BCVA and NV regression, with no potential increased incidence of AEs, which proves that the combination therapy is an efficient therapeutic strategy that could improve the management of patients with DR.